Histopathological comparison of the onset of peri‐implantitis and periodontitis in rats. Issue 2 (25th January 2016) - Takamori, Yuzo; Atsuta, Ikiru; Nakamura, Hirotaka; Sawase, Takashi; Koyano, Kiyoshi; Hara, Yoshitaka
Abstract: Background and objective: There are a few experimental models that clearly describe the pathological differences in tissue destruction between periodontitis and peri‐implantitis. We recently reported that the formation of immune complexes accelerates site‐specific loss of attachment and alveolar bone resorption when an antigen is topically applied in the gingival sulcus of an immunized rat. We applied this model to the peri‐implant tissues and compared peri‐implant destruction to periodontitis without using a ligature. Material and methods: Twenty‐five rats were used in this study and were divided into five groups. Implantation was performed immediately after extraction of right first molars in rats. The left first molars were left untreated to be examined as natural teeth. The immunized group consisted of rats that had received intraperitoneal lipopolysaccharide (LPS), whereas the nonimmunized group received only phosphate‐buffered saline (PBS). The untreated baseline group received only implantation. After intraperitoneal booster injection, half of each group received topical application of LPS in the palatal gingival sulcus daily for 3 days. The other half of the groups received PBS. Histopathological and histometrical findings were observed with hematoxylin and eosin staining, collagen fibers were observed with Azan staining, and formation of immune complexes was immunohistologically evaluated by C1qB expression. Result: Peri‐implant tissue destruction was greater in the immunized and LPS‐applied groups than in the other groups. No periodontal destruction was observed. Formation of immune complexes was observed in the junctional epithelium and adjacent connective tissue in the immunized groups. Conclusion: Antigen‐induced peri‐implant tissue destruction occurs faster than periodontal tissue destruction.